Bacterial bloodstream infections in level-I trauma intensive care unit in Serbia: incidence, causative agents and outcomes - Djuric, Olivera; Markovic-Denic, Ljiljana; Jovanovic, Bojan; Jovanovic, Snezana; Marusic, Vuk; Bumbasirevic, Vesna (The Journal of Infection in Developing Countries, 2018)
Introduction: We aimed to describe incidence, outcomes and antimicrobial resistance markers of causative agents of bacterial BSI in the intensive care unit (ICU) in a trauma center in Serbia. Methodology: Prospective surveillance was conducted from November 2014 to April 2016 in two trauma-surgical ICUs of the Emergency Department of Clinical center of Serbia. Bloodstream infections were diagnosed using the definitions of Center for Disease Control and Prevention. Results: Out of 406 trauma patients, 57 had at least one episode of BSI (cumulative incidence 14.0%). Overall 62 BSI episodes were diagnosed (incidence rate 11.8/1000 patient/days), of which 43 (69.4%) were primary BSI (13 catheter-related BSI and 30 of unknown origin) and 19 (30.6%) were secondary BSI. The most common isolated pathogen was Acinetobacter spp. [n = 24 (34.8%)], followed by Klebsiella spp. [n = 17 (24.6%)] and P. aeruginosa [n = 8 (1.6%)]. All S. aureus [n = 6 (100%)] and CoNS [n = 3 (100%)] isolates were methicillin resistant, while 4 (66%) of Enterococci isolates were vacomycin resistant. All isolates of Enterobacteriaceae were resistant to third-generation cephalosporins [n = 22 (100%)] while 7 (87.5%) of P. aeruginosa and 23 (95.8%) of Acinetobacter spp. isolates were resistant to carbapenems. All-cause mortality and sepsis were significantly higher in trauma patients with BSI compared to those without BSI (P < 0.001 each). Conclusions: BSI is a common healthcare-associated infection in trauma ICU and it is associated with worse outcome. Better adherence to infection control measures and guidelines for prevention of primary BSI must be achieved.